Managing end-of-life decisions in critical infants: a survey of neonatologists in Cordoba, Argentina - Silberberg, Agustín Alfredo (2013)
The number of preterm births has significantly increased in the last few decades (1). Doctors face new situations that call for a cautious medical approach, especially in relation to newborns whose survival is considered doubtful (2). Some infants are discharged alive, some die and the frequency of disabled children is uncertain. All this has raised ethical issues, such as the management of neonates with disabilities, circumstances where only palliative care is recommended and refusal of life-sustaining treatment (LST) where death is imminent or the infant could develop severe sequelae. There is currently widespread discussion on these subjects, with different opinions based on diverse anthropological viewpoints that influence medical decisions (3). In view of these ongoing debates, we carried out a survey of neonatologists in Cordoba, Argentina, to determine their medical decisions concerning the care of neonates.